< >

 Conversation Between IIMarckus and PlatniumPiano

Notices

Conversation Between IIMarckus and PlatniumPiano
Showing Visitor Messages 1 to 4 of 4
1. December 23rd, 2008 2:37 PM
PlatniumPiano
Lol good job.

2. December 23rd, 2008 2:12 PM
IIMarckus
A(A+B-X)=-B(A+B-X)
__________________
(A+B-X)

Which I assume translates to A(A + B − X) ÷ (A + B − X) = −B(A + B − X) ÷ (A + B − X). A = −B is a valid result from this step in all cases but one: when A + B − X = 0, because division by zero is undefined. Since the second line (A + B = X) specifically states that it is zero, the proof is invalid.

You can see a similar error in this proof.
3. December 23rd, 2008 8:52 AM
PlatniumPiano
Lol. yes that was a typo- (A+B)(A+B).
The fourth step i have A= -B. This is 0. Therefore, A+B= 0, if you add the B to the side with the A. Now there is nothing there (0), so A+B=0.
4. December 22nd, 2008 10:59 PM
IIMarckus
The math in your signature is faulty…
(A+B)A+B=X(A+B) should be (A+B)(A+B)=X(A+B), though this is probably just a typo.

The real problem with the math is in the fourth step. A + B − X = 0, so what you actually have is
A × 0 = B × 0

Which is, of course, true. Then you try to divide by zero. However, 0 ÷ 0 ≠ 1! Division by zero is undefined.

All times are GMT -8. The time now is 3:01 PM.